2017
DOI: 10.1186/s40536-017-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ participation in professional development concerning the implementation of new technologies in class: a latent class analysis of teachers and the relationship with the use of computers, ICT self-efficacy and emphasis on teaching ICT skills

Abstract: The increasing availability of new technologies in an ever more digitalized world has gained momentum in practically all spheres of life, making technology-related skills a key competence not only in professional settings. Thus, schools assume responsibility for imparting these skills to their students, and hence to future generations of professionals. In so doing, teachers play a key role with their competences in using new technologies constituting an essential prerequisite for the effective implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 23 publications
1
34
1
3
Order By: Relevance
“…Teachers involved in ICT professional development definitely tend to use computers more often, place more emphasis on teaching ICT skills, and have a stronger sense of ICT self-efficacy than their skeptical colleagues [35].…”
Section: Discussionmentioning
confidence: 99%
“…Teachers involved in ICT professional development definitely tend to use computers more often, place more emphasis on teaching ICT skills, and have a stronger sense of ICT self-efficacy than their skeptical colleagues [35].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary analyses of ICILS 2013 suggest that teacher attitudes are associated with the extent and the ways that they use ICT in their teaching (Drossel et al 2017a;Eickelmann and Vennemann 2017). Similar analyses investigated the influence of professional development on teacher attitudes to, and use of, ICT in school education (Drossel and Eickelmann 2017). In fact, there is evidence that school factors, including teachers' collaborative use of ICT, can shape the pedagogical use of ICT for teaching purposes (Drossel et al 2017b;Gerick et al 2017).…”
Section: Research On the Use Of Digital Technologies In Learningmentioning
confidence: 97%
“…In this context, several studies have found that teacher cooperation in general can be intensified through the use of ICT and that more intensive forms of teacher cooperation can have a positive effect on teachers' use of ICT for teaching and learning (cf. Drossel and Eickelmann 2017;Tondeur et al 2012). Despite of the positive effects attributed to teacher cooperation for teaching and learning with ICT at school, the findings of IEA-ICILS 2018 were able to show that teacher cooperation is subject to variation with respect to two aspects (cf.…”
Section: Teacher Cooperationmentioning
confidence: 97%